Warm glow and embedding in contingent valuation - Paulo A. L. D. Nunes; Erik Schokkaert (Fondazione Eni Enrico Mattei (FEEM), 2001)
This paper reports the results from a contingent valuation study designed to investigate the influence of warm glow in willingness-to-pay responses. Interindividual differences in warm glow motivation are measured through a factor analysis, performed on a list of attitudinal items. The reported willingness to pay measures fail to pass the scope test. Both socioeconomic variables and motivational factor scores are significant in the explanation of the individual WTP measures. We compute dry WTP measures by taking out the effect of the warm glow motivation. These dry measures satisfy both the scope test and Hausman's adding-up property and could therefore be interpreted as reflecting true economic preferences.
Keywords: C12; C13; C14; Q26; 330; Contingent valuation; recreation; wildlife; willingness to pay; warm glow; Willingness to pay; Artenvielfalt; Freizeit; Schutzgebiet; Theorie; Portugal